USING DORA THE EXPLORER CARTOON MOVIE SERIES TO FACILITATE THE MASTERY OF SELECTED CHILDREN’S VOCABULARY - Phan Yunianti Wijaya; Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2023)
Vocabulary is the key for learners to be able to communicate effectively in English. The research using Dora the Explorer cartoon movie to recognize English vocabulary mastery for children. This study is aimed to find out whether the use of Dora the Explorer cartoon movie can be facilitated in the learning of children’s selected vocabularies. The participants of this study were 16 students of PAUD MULIA. This research method employs descriptive qualitative data collection via observation, documentation, pre-test, and post-test. The instrument used was an oral test with flashcards. The results show that selected children's vocabulary increased significantly after watching the English cartoon movie. Finally, the use of the Dora the Explorer cartoon movie can help with specific vocabulary mastery. Aside from that, the children appear engaged and enthusiastic while learning. Keywords: Facilitated, Vocabulary, Cartoon movie, Dora the Explorer.